Exploring ultrasound-induced metabolic attenuation in Lacticaseibacillus casei ATCC 393—A combined approach using traditional methods and flow cytometry - Giordano, Irene; Salman, Mohammed; Arioli, Stefania; Mora, Diego; Mauriello, Gianluigi (Frontiers in Microbiology, 2025)
Attenuation technologies applied to probiotics aim to modulate specific metabolic pathways, particularly acidification, while maintaining cell viability. Although ultrasound is an emerging tool in this context, its precise mechanism of action on probiotic cells remains poorly understood. The study aimed to establish a suitable method to investigate the effects of ultrasound attenuation on probiotics. Lacticaseibacillus casei ATCC 393 was exposed to sonication for 6 and 8 min in a water suspension. Morphological changes, cultivability, acidification capacity, and growth recovery were assessed using culture-dependent methods. Flow cytometry (FCM) combined with fluorescent staining was used to evaluate membrane integrity (as a marker of viability) and esterase activity (as a marker of metabolic activity). Moreover, plate count and FCM data were compared to estimate the overall effect of ultrasound. A reduction in cell size was observed, which was confirmed by decreases in forward and side scatter signals. Acidification capacity was dependent on the intensity applied, and only the 8-min treatment induced prolonged modulation over 24 h. Esterase activity was similarly affected by both sonicating times, whereas membrane integrity reduction was dependent on the treatment intensity. The probiotic demonstrated the ability to restore growth, with recovery time proportionally increasing with the duration of ultrasound treatment. Direct comparisons of the viable, culturable, and metabolically active subpopulations indicate that they are similarly affected by 6 min of sonication. On the contrary, 8 min of sonication increased sample heterogeneity, generating three different subpopulations. The lack of overlap between viable and culturable clusters suggested that the cells that were sonicated for 8 min entered the viable but non-culturable state. These results provide insight into the intensity-dependent effects of ultrasound on probiotic functionality and demonstrate the value of integrative analytical approaches (FCM combined with traditional methods) for characterizing bacterial responses to attenuation strategies.